What are the Main Variables that Influence the Dynamics of Ecuador's Sovereign Risk? - Carrillo Maldonado, Paúl (2021)
TThe objective of this study is to identify the main variables that determine the dynamics of the interest rate spread of international bonds issued by the Ecuadorian government. Use the Emerging Market Bond Index (EMBI) or country risk to understand the determinants of the cost of Ecuador's public debt. In principle, the EMBI is the interest rate premium on US bonds that investors will demand to invest in Ecuador's sovereign bonds and is therefore often interpreted as a measure of the country's sovereign risk level (Longstaff et al., 2011). This work is related to del Cristo and Gómez-Puig (2017), who show that the country risk of dollarized economies (Panama and Ecuador) shows a more stable dynamic than other Latin American economies, such as Argentina or Brazil. Furthermore, their results suggest that international factors are more important than national variables in explaining the variation in sovereign spreads. We believe that empirical contributions have not yet been made to identify `` all '' the national and international variables that determine the dynamics of the Ecuadorian EMBI. Díaz-Cassou and Ruiz-Arranz (2018) qualitatively show that the international price of oil is the main variable that explains the evolution of Ecuador's country risk. del Cristo and Gómez-Puig (2017) use a vector autoregressive model with a correction equation, concluding that public debt is the most important internal determinant of sovereign spreads in Ecuador.